2004
DOI: 10.1016/s0002-9440(10)63110-0
|View full text |Cite
|
Sign up to set email alerts
|

Progression in Cutaneous Malignant Melanoma Is Associated with Distinct Expression Profiles

Abstract: Cutaneous malignant melanoma remains the leading cause of skin cancer death in industrialized countries. Clinical and histological variables that predict survival, such as Breslow's index, tumor size, ulceration, or vascular invasion have been identified in malignant melanoma. Nevertheless, the potential relevance of biological variables still awaits an in-depth exploration. Using tissue microarrays (TMAs), we retrospectively analyzed 165 malignant melanoma samples from 88 patients corresponding to distinct hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
201
3
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 227 publications
(246 citation statements)
references
References 39 publications
16
201
3
11
Order By: Relevance
“…These data are in accord with literature reports of negative or weak expression of cyclin D1 in benign melanocytic lesions and high levels in cutaneous melanomas [22][23][24][25]. Besides cutaneous melanomas, increased expression of cyclin D1 has been reported in uveal melanomas, and now we also confirm in oral melanomas, suggesting that it has an oncogenic role in the pathogenesis of this aggressive neoplasm [13,24,26]. Some studies have also shown that cyclin D1 is associated with unfavorable outcomes in cutaneous melanomas and is an independent risk factor for the development of metastases [25,26].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These data are in accord with literature reports of negative or weak expression of cyclin D1 in benign melanocytic lesions and high levels in cutaneous melanomas [22][23][24][25]. Besides cutaneous melanomas, increased expression of cyclin D1 has been reported in uveal melanomas, and now we also confirm in oral melanomas, suggesting that it has an oncogenic role in the pathogenesis of this aggressive neoplasm [13,24,26]. Some studies have also shown that cyclin D1 is associated with unfavorable outcomes in cutaneous melanomas and is an independent risk factor for the development of metastases [25,26].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with these results, cutaneous nevi have been shown to be uniformly positive for p16 in more than 70% of cells [7,15]. On the other hand, loss of p16 expression has also been demonstrated in almost 50% of primary cutaneous and oral melanomas, similarly to many other cancers, including pancreatic, esophageal, lung, head and neck, breast, bladder, brain and ovarian [1,5,13,14]. Although there is general consensus regarding the loss of p16 expression in cutaneous melanomas, it is suggested that this occurs in later stages of the disease, as it is not altered in melanoma in situ [16].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations